West Nile virus infections in France, July to November 2018. (13th November 2019) - Ramalli, L; Grard, G; Beck, C; Gallian, P; L'Ambert, G; Desvaux, S; Jourdan, M; Ortmans, C; Paty, M-C; Franke, F
Abstract: : In July 2018, one autochthonous case of West Nile virus (WNV) infection was identified in Nice, Provence-Alpes-Côte d'Azur (Paca). We investigated to determine the potential place of infection and the extent of viral circulation in the area, in order to guide control and preventive measures. In affected areas, we raised awareness of health professionals on WNV infections, substance of human origin safety relied on nucleic acid testing for WNV and on deferral of blood donors indicating minimum one night of stay in the areas for 28 days. Equine, wild bird and entomologic surveillance activities were reinforced. The human arboviruses national reference laboratory (NRL) retrospectively tested samples from hospitalized individuals from June 1st with meningitis and encephalitis around Nice. We tested negative suspected autochthonous cases of chikungunya and dengue infections notified since July in Paca and presenting WNV compatible symptoms. Measures were adapted along identification of additional cases. We identified 27 autochthonous cases, with onset of symptoms between July 7th and November 12th: 24 in Paca, 2 in Corsica and 1 in Occitanie. Seven cases presented neuroinvasives symptoms, 18 flu-like symptoms and 2 were asymptomatic. One blood donation and 2 organs tested positive for WNV. The animal NRL identified 13 equine cases (1 in Paca, 5 in Corsica and 7 in Occitanie) and 4 infected raptors with nervous symptoms (3 in Paca and 1 in Corsica). Genomic characterization of the virus identified a strain belonging to the lineage 2 among 2 raptors. No virus was found in mosquitoes captured in affected areas. Since 2000, six episodes of WNV transmission were reported in France but none with this extent. For the first time, the lineage 2, circulating in Italy and other European countries, was isolated in France which might be changing epidemiological situation. Therefore, surveillance activities should be revised in order to promptly secure blood products. Key messages: We describe the most important episode of West Nile Virus transmission identified in humans in France. In 2018, West Nile virus lineage 2 was isolated for the first time in France which might change the epidemiological situation in the country.